Maritime Education Enhancement Through Graduate Experience Analysis - Ahmad Wahid; Tri Cahyadi; Larsen Barasa; Amrin Amrin (Meteor STIP Marunda, 2025)
This qualitative research investigates the effectiveness of maritime vocational education through a comprehensive analysis of thirty graduates from nautical deck engineering, naval marine engineering, and port and shipping engineering programs. The study employs thematic analysis of in-depth interviews to examine professional competency development, sustainability awareness, and industry-academia alignment in maritime education outcomes. Results indicate strong technical competency development (91% high proficiency) and practical training effectiveness (90% satisfaction), while revealing significant gaps in communication skills (68% adequacy), technology integration (61% satisfaction), and sustainability education (69% awareness). Cross-specialization analysis demonstrates varying competency patterns, with port and shipping graduates showing the highest business acumen and sustainability awareness, while all specializations require enhanced Maritime English and digital technology competencies. The research identifies communication skills, technology integration, and sustainability education as priority areas for enhancing graduate professional preparedness and industry alignment. These findings contribute to maritime education policy development and curriculum enhancement initiatives, offering evidence-based guidance for improving industry-academia collaboration. The study validates experiential learning approaches in maritime education while highlighting the need for adaptation to contemporary industry demands, including digitalization, environmental consciousness, and international communication requirements essential for global maritime operations.